Enhanced Stability and In Vitro Biocompatibility of Chitosan-Coated Lipid Vesicles for Indomethacin Delivery - Angy Abu Koush; Eliza Gratiela Popa; Daniela Angelica Pricop; Loredana Nita; Cezar-Ilie Foia; Ana-Maria Raluca Pauna; Beatrice Rozalina Buca; Liliana Lacramioara Pavel; Liliana Mititelu-Tartau (Pharmaceutics)
Background: Lipid vesicles, especially those utilizing biocompatible materials like chitosan (CHIT), hold significant promise for enhancing the stability and release characteristics of drugs such as indomethacin (IND), effectively overcoming the drawbacks associated with conventional drug formulations. Objectives: This study seeks to develop and characterize novel lipid vesicles composed of phosphatidylcholine and CHIT that encapsulate indomethacin (IND-ves), as well as to evaluate their in vitro hemocompatibility. Methods: The systems encapsulating IND were prepared using a molecular droplet self-assembly technique, involving the dissolution of lipids, cholesterol, and indomethacin in ethanol, followed by sonication and the gradual incorporation of a CHIT solution to form stable vesicular structures. The vesicles were characterized in terms of size, morphology, Zeta potential, and encapsulation efficiency and the profile release of drug was assessd. In vitro hemocompatibility was evaluated by measuring erythrocyte lysis and quantifying hemolysis rates. Results: The IND-ves exhibited an entrapment efficiency of 85%, with vesicles averaging 317.6 nm in size, and a Zeta potential of 24 mV, indicating good stability in suspension. In vitro release kinetics demonstrated an extended release profile of IND from the vesicles over 8 h, contrasting with the immediate release observed from plain drug solutions. The hemocompatibility assessment revealed that IND-ves exhibited minimal hemolysis, comparable to control groups, indicating good compatibility with erythrocytes. Conclusions: IND-ves provide a promising approach for modified indomethacin delivery, enhancing stability and hemocompatibility. These findings suggest their potential for effective NSAID delivery, with further in vivo studies required to explore clinical applications.